2007
DOI: 10.1152/ajpheart.01071.2006
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ischemic preconditioning's cardioprotection in aged mouse hearts is associated with reduced gap junctional and mitochondrial levels of connexin 43

Abstract: Boengler K, Konietzka I, Buechert A, Heinen Y, Garcia-Dorado D, Heusch G, Schulz R. Loss of ischemic preconditioning's cardioprotection in aged mouse hearts is associated with reduced gap junctional and mitochondrial levels of connexin 43. Am J Physiol Heart Circ Physiol 292: H1764 -H1769, 2007. First published December 1, 2006; doi:10.1152/ajpheart.01071.2006 is localized at left ventricular (LV) gap junctions and in cardiomyocyte mitochondria. A genetically induced reduction of Cx43 as well as blockade of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
107
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 44 publications
13
107
0
Order By: Relevance
“…The gap junction connexin 43 content has been tightly involved in the development of rigor tension, since it facilitates cell-to-cell communication and generalization of the behavior of a cell minority to the total cellular population of the heart. It is known to be decreased with aging, starting precisely at middle duration of the lifespan (Boengler et al 2007). Since middle age reduces the gap junction connexin 43 content, excess proton accumulated in the most metabolically active cells should not be easily diffused in the less active cells, which should delay PFK inhibition in these last cells and allow the upholding of their metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The gap junction connexin 43 content has been tightly involved in the development of rigor tension, since it facilitates cell-to-cell communication and generalization of the behavior of a cell minority to the total cellular population of the heart. It is known to be decreased with aging, starting precisely at middle duration of the lifespan (Boengler et al 2007). Since middle age reduces the gap junction connexin 43 content, excess proton accumulated in the most metabolically active cells should not be easily diffused in the less active cells, which should delay PFK inhibition in these last cells and allow the upholding of their metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of aging on PC is unclear. Some studies [27,28,29] but not others [30] support the concept that the early PC response is absent in old animals. Aging abolishes the late phase of ischemia-induced PC in mice [31] but not the late phase of opioid-induced late PC in rats [32].…”
Section: Cox-2 Involvement In Pcmentioning
confidence: 99%
“…The annealing temperature was 61.8°C, 54.9°C and 54.7°C for Cx43, eNOS and GAPDH, respectively. The expression level of Cx43 mRNA was normalized with eNOS mRNA because there was no significant difference between adult rats and aged rats (Boengler et al 2007) and GAPDH mRNA expression.…”
Section: Reverse Transcription and Pcr Amplification (Rt-pcr)mentioning
confidence: 99%
“…It has been reported that vagal nerve stimulation (VNS) exerts an anti-arrhythmic effect by preserving phosphorylated Cx43 in a rat model of MI (Ando et al 2005). However, previous reports found that the expression of Cx43 protein is decreased in the ventricles of aged rats (Boengler et al 2006(Boengler et al , 2007(Boengler et al , 2009). Whether VNS can exert an anti-arrhythmic effect during acute MI in aged rats remains unknown.…”
mentioning
confidence: 99%